The old rectory the story of the English parsonage - Jennings, Anthony (Anthony J. S.) (London : Continuum, 2009)
Pevsner described the pairing of church and parsonage as a feature of the English village unparalleled on the Continent. John Betjeman saw the design of rectories and vicarages as highly influential on our architecture. Forsaken by the Church but coveted by the private buyer, this is the story of these quintessentially English houses, with their combination of fine architecture, charm and character, large gardens and often splendidly rural locations. The Old Rectory examines their history, their evolution through the centuries, their many and varied styles of architecture, and their place in o
Foreword; List of Illustrations in text; List of Colour and Black and White plates; Introduction; PART ONE -- PROLOGUE; PART TWO -- THE HISTORY; PART THREE -- THE ARCHITECTURE; PART FOUR -- THE PRESENT; PART FIVE -- THE LEGACY; PART SIX -- THE FUTURE; Acknowledgements; APPENDICES; Bibliography; Index of Houses and Places; Index of Architects; General Index
Includes bibliographical references (p. 261-265) and index.
Description based on print version record.
Keywords: Parsonages -- England -- History; Architecture, Domestic -- England -- History; Parsonages -- Social aspects -- England; Parsonages -- England -- Pictorial works; Clergy -- Dwellings -- England -- History; Architecture; RELIGION -- Christian Ministry -- Pastoral Resources; Electronic books